2017
DOI: 10.22336/rjo.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

CAN Optical Coherence Tomography redefine amblyopia?

Abstract: REVIEW 95Results: 19 research studies focused on macular and nerve optic changes, 7 on choroidal changes and 6 on retinal changes after occlusion. The results were discussed according to the type of amblyopia, alteration of macular thickness, optic nerve changes, ganglion cell layer changes, and alteration of choroidal thickness. Conclusions:The results are of great variability, and it seems that macula and choroid involvement is more frequently suggested compared with optic nerve involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Some OCT studies have suggested few changes on OCT in these eyes. [123] Some observers have analyzed the changes in the macular thickness in different types of amblyopia at different distances from the center of the fovea with variable conclusions. Few studies have shown an increase in the foveolar thickness and decrease in the macular thickness away from the center in the amblyopic eyes as compared with normal/control eyes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some OCT studies have suggested few changes on OCT in these eyes. [123] Some observers have analyzed the changes in the macular thickness in different types of amblyopia at different distances from the center of the fovea with variable conclusions. Few studies have shown an increase in the foveolar thickness and decrease in the macular thickness away from the center in the amblyopic eyes as compared with normal/control eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have shown an increase in the foveolar thickness and decrease in the macular thickness away from the center in the amblyopic eyes as compared with normal/control eyes. [13] Few authors have demonstrated a reduction in macular thickness after patching therapy. [4] Similarly, the retinal nerve fiber layer (RNFL) thickness around the peripapillary region in amblyopia has been studied with variable conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study using OCT demonstrated that the subfoveal choroidal thickness (CT) is statistically the same in both AE and FE [20]. But contrary to these findings, other OCT studies have often shown that the subfoveal CT is increased in AE [21]. It is difficult to compare other OCT studies to ours since most of them studied thickness which, in many cases, does not affect the mean reflectivity of a given structure.…”
Section: Plos Onementioning
confidence: 73%